El Debate Moderno Sobre Los Escritos Económicos Aristotélicos - Borisonik, Hernán (The modern debate on the Aristotelian economic writings., 2013)
The present article is a critical reading of the most important modern interpretations on Aristotle's economic writings. Firstly, the debate between the “primitivists" and the “modernists" (headed by Rodbertus, Bücher and Meyer) will be studied. Then, the readings of Karl Marx, Joseph Schumpeter, Karl Polanyi and Moses Finley, will be analyzed, considering these authors as the most renowned commentators of the Aristotelian economical legacy. (English)
Political Science
Keywords: ARISTOTLE; Aristóteles; FINLEY; M. I. (Moses Israel); 1912-1986; MARX; Karl; 1818-1883; SCHUMPETER; Joseph Alois; 1883-1950; economic research; economics; economía; history of economics; primitivism and modernism; primitivismo y modernismo

Los aborígenes colombianos y las paradojas del desarrollo: el caso de los emberá katíos del Alto Sinú - Martínez Triviño, Ana Milena; Reyes Albarracín, Fredy Leonardo (Colombian indigenous and the paradoxes of development: the case of the emberá katios from High Sinú., 2013)
In 1992 the construction of the Urra I hydroelectric begins, one of the most ambitious energy projects in the recent history of Colombia. Located in the inhospitable jungle region of High Sinú -northwest of the Andean territory- the environmental license granted by government entities ignored the ecological and environmental impacts the work would entail, and also failed to recognize the presence of the emberákatio indigenous people, whose constitutional rights were violated. Following the arguments presented by the economist Karl Polanyi, the article explores the environmental, social and cultural consequences caused by the energy project, in addition to delving in the strategy of violence and extermination that paramilitarism created to disrupt the organizational processes for the emberákatios, which resulted in the disappearance and murder of indigenous leaders. (English)
Political Science; International Relations
Keywords: aborígenes; fictitiuos merchanidise; indigenous; mercado autorregulado; mercancías ficticias; paramilitarism; paramilitarismo; self-regulated market; violence; violencia

Karl polanyi and the economicist hybris of modernity - Polo Blanco, Jorge (Logos (Spain), 2013)
Using the work of Karl Polanyi as its axis, this study attempts to sketch a criticism of economicism and of the society that produces it, a society launched on a historical cultural path that may well be understood as a gradual economic totalization of human life. That is the critical path which will be posed here, if only in an embryonic manner.
Economics
Keywords: economic determinism; economic totalization; economicism